Reelection or term limits? The short and the long run view of economic policy - Streb, Jorge (Estudios de Economía, 2016)
An incumbent's drive for reelection can lead to political budget cycles. The distortion cycles cause in economic policy may be offset by the information they indirectly provide about the incumbent's competency. The informative content of cycles depends on the sophistication of voters, i.e. on whether they are rational or near rational. In a framework of individual candidates, constitutional clauses that prohibit the reelection of the president eliminate political budget cycles. One-term limits that allow non-immediate reelection also shift the focus from short-run cycles to the long-run soundness of economic policies, and have superior welfare properties. Hence, the choice is not reelection or not, but rather immediate or non-immediate reelection.